Discrepancies in addressing overdose prevention through prescription monitoring programs. (1st August 2015) - Green, Traci C.; Bowman, Sarah; Davis, Corey; Los, Cristina; McHugh, Kimberly; Friedmann, Peter D.
Highlights: We reviewed 47 prescription monitoring program (PMP) websites for overdose content. Most PMPs did not address overdose or related terms in available materials. Few state PMPs project overdose-specific messaging or provider tools for prevention. Comprehensive public health overdose prevention messaging is uncommon among PMPs. Abstract: Background: State prescription monitoring programs (PMPs) purport to address the prescription opioid epidemic, but have evidenced limited effect on reducing opioid-related mortality. Methods: We systematically reviewed publicly available, PMP web-based materials from December, 2012 to October, 2013, to assess the degree to which overdose prevention was articulated in state PMP goals, mission statement, and accessible educational materials. The sites and available resources of 47 state PMPs with a web presence were reviewed by two independent coders for use of "overdose" and related terms. Website materials were further coded to capture five general thematic orientations: supply reduction-therapeutic, supply reduction-punitive, demand reduction, public health/research, and harm reduction oriented in content. Results: Twenty-nine of 47 (62%) PMPs did not address overdose or related terms in available online materials; six (12.8%) contained overdose-oriented messaging; and two included specific overdose prevention tools for providers. There were a median of three thematic orientations represented on the 18 state PMP websites mentioning only the term overdose, compared with a median of 4.5 thematic domains on the six PMP websites with overdose-oriented content. Conclusions: A more comprehensive, public health orientation for PMPs that explicitly and publicly articulates their application and role in overdose prevention may increase PMP effectiveness and use.